3 kW, 0.2 nm narrow linewidth linearly polarized all-fiber laser based on a compact MOPA structure. (29th May 2020) - Wang, Yanshan; Ke, Weiwei; Peng, Wanjing; Chang, Zhe; Feng, Yujun; Sun, Yinhong; Gao, Qingsong; Ma, Yi; Zhu, Rihong; Tang, Chun
Abstract: In this work, we realize a high-power, narrow linewidth, linearly polarized laser output based on a compact all-fiber polarization maintaining (PM) master oscillator power amplifier. The seed is a fiber oscillator laser (FOL) with few-longitudinal-mode for spectral broadening suppression. The spectral broadening characteristics in the FOL seed and in the PM-amplifier with different pumping schemes are studied experimentally and theoretically. The effect of different types of fibers in the amplifier on spectral broadening is also analysed theoretically. Finally, we demonstrate a narrow linewidth linearly polarized all-fiber amplifier operating at the maximum output power of 3.08 kW with a 3 dB linewidth of 0.2 nm. The polarization extinction ratio is measured to be larger than 93.5% and the M 2 maintains lower than 1.45 in the power scaling process. To the best of our knowledge, this is the highest demonstrated output power for narrow linewidth linearly polarized all-fiber lasers with the charactristics of low cost and a compact structure.